Analysis of Financial Performance in Kendari City Government (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to analyze the Financial Performance of the Kendari City Government in 2019-2022. This research is quantitative research with a descriptive method. The data analyzed are the independence ratio, the effectiveness ratio, the efficiency ratio, the activity ratio, and the growth ratio of Regional Own Revenue in Kendari City in 2019-2022. The results showed that the financial performance of the Kendari City local government based on the independence ratio was classified as very low with a percentage of 19.69%, financial performance based on the average PAD effectiveness ratio was not effective with a percentage of 53.74%, financial performance based on the average activity ratio operating expenditures did not go well with a percentage of 70.27%, the average ratio of capital expenditures also did not go well which only had a percentage value of 134.59%, financial performance based on the average PAD growth was said to be unsuccessful because it only had a percentage of 12, 37%. Keywords: Regional Financial Performance; Activity Ratio; Effectiveness Ratio; Efficiency Ratio; Independence Ratio; Growth Ratio.